The Ōuchi-Spillmann Illusion Revisited. (April 2013) - Spillmann, Lothar
In a disk – ring pattern composed of horizontally oriented checks in the centre and vertically oriented checks in the surround, the centre appears to slide relative to the surround when the pattern is slowly moved about. This phenomenon has been called the Ōuchi illusion. Slow sliding movements may represent involuntary ocular drifts, while occasional jerks suggest a contribution by microsaccades. The conditions under which the illusion occurs both with free viewing and in the absence of involuntary eye movements are reviewed. Illusory sliding is most pronounced with diagonal movement of the stimulus pattern, resulting in apparent motion orthogonal to the orientation of the disk. The illusion requires checks of low spatial frequency; it persists with low luminance contrast and blur of the inducing pattern, but is absent at equiluminance. These results suggest a magnocellular neuronal mechanism. Sliding continues to be seen with an empty annular zone separating centre and surround, and is seen even when there is no concentric surround at all, just two abutting flanks. Nine hypotheses proposed to account for the illusory motion of the centre relative to the surround are reviewed. Among these the models based on an integration bias of local motion vectors (Mather 2000 Perception 29 721–727) and Type II plaid motion (Ashida 2002 Vision Research 42 1413 – 1420) come closest to explaining illusory sliding in the Ōuchi figure, but open questions remain. Specifically, more research is warranted to correlate the predicted with the perceived direction of sliding motion in both check and grating patterns.